Islamic Banking and Economic Integration in Thailand: Opportunities and Challenges in a Minority-Muslim Context - Miss Fatihah Saman (PT. Hassan Group Publisher, 2025)
The development of Islamic banking in Thailand presents unique dynamics within a minority-Muslim context. This study aims to examine the opportunities and challenges of Islamic banking in Thailand, particularly in relation to regional economic integration and financial inclusion of Muslim communities. The research employed a qualitative descriptive method through literature review, policy analysis, and comparative study with Islamic banking practices in other ASEAN countries. The findings reveal that Islamic banking in Thailand faces constraints such as limited regulatory frameworks, low financial literacy, and a shortage of trained professionals, yet opportunities exist through ASEAN integration, digital innovation, and sustainable policy support. The implications highlight the need for stronger regulations, institutional capacity building, and regional cooperation to position Islamic banking as an inclusive instrument within the national financial system